2002
DOI: 10.2118/78812-pa
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rock Plasticity on Hydraulic Fracture Propagation and Closure

Abstract: We performed scaled laboratory experiments of hydraulic fracture propagation and closure in soft artificial rock and outcrop rock samples. We also performed numerical simulations of the fracture behavior in plastic rocks with independently measured rock properties. The simulations aided in interpreting the measurements and extrapolating the results to field scale.Compared with elastic rock, plasticity induces a larger width for a given net pressure. However, the pressure to propagate fractures is only marginal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…The unconsolidated nature of the material means that if an opening is created, the tip of the opening cannot sustain large stress contrast, and plastic yielding is expected. Influence of plasticity in hydraulic fracturing has been examined for both cohesive and cohesionless materials [Papanastasiou and Thiercelin, 1993;van Dam et al, 2002;Abou-Sayed et al, 2004;Papanastasiou and Atkinson, 2006;Wu, 2006]. In general, one-dimensional leakoff model [Carter, 1957] is assumed for fluid flow from the fracture faces to the matrix in conventional LEFM-based models.…”
Section: Background and Experimental Motivationmentioning
confidence: 99%
“…The unconsolidated nature of the material means that if an opening is created, the tip of the opening cannot sustain large stress contrast, and plastic yielding is expected. Influence of plasticity in hydraulic fracturing has been examined for both cohesive and cohesionless materials [Papanastasiou and Thiercelin, 1993;van Dam et al, 2002;Abou-Sayed et al, 2004;Papanastasiou and Atkinson, 2006;Wu, 2006]. In general, one-dimensional leakoff model [Carter, 1957] is assumed for fluid flow from the fracture faces to the matrix in conventional LEFM-based models.…”
Section: Background and Experimental Motivationmentioning
confidence: 99%
“…The pressure at the moment a fracture closes is widely accepted as the minimum confining stress acting normal to the fracture [6]. Recent experiments have shown that in some cases fractures could close at pressures that differ from the confining stress, a finding that is at odds with some stress testing interpretations [76]. Recent analyses of the process of hydraulic fracture closure (e.g.…”
Section: Analysis Of a Deformable Fracturementioning
confidence: 99%
“…Recent analyses of the process of hydraulic fracture closure (e.g. References [76][77][78]) have assumed uniform pressure and effective stress in the fracture, and have used simplified analyses of leakoff. It seems reasonable to expect that flow within a hydraulic fracture during closure will affect the pressure log, so the approach described above could improve interpretations of stress tests and explanations of laboratory tests.…”
Section: Analysis Of a Deformable Fracturementioning
confidence: 99%
“…The commonly used pseudo 3D fracture models that use stress intensity factor based criteria for the fracture propagation problem do not explicitly include pore pressure. Recent experimental work indicates that the LEFM approach for fracture propagation is not always valid and a cohesive zone description is necessary (Van Dam and de Pater, 2001;2002). Such cohesive zone models (CZM) would then use effective stress at the tip exceeding tensile strength as a propagation criterion which introduces the effect of pore pressure.…”
Section: Introductionmentioning
confidence: 99%